2020
DOI: 10.3389/fmicb.2020.00885
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genome Structure of Virulent Phage EspM4VN to Control Enterobacter sp. M4 Isolated From Plant Soft Rot

Abstract: Enterobacter sp. M4 and other bacterial strains were isolated from plant soft rot disease. Virulent phages such as EspM4VN isolated from soil are trending biological controls for plant disease. This phage has an icosahedral head (100 nm in diameter), a neck, and a contractile sheath (100 nm long and 18 nm wide). It belongs to the Ackermannviridae family and resembles Shigella phage Ag3 and Dickeya phages JA15 and XF4. We report herein that EspM4VN was stable from 10 • C to 50 • C and pH 4 to 10 but deactivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Our analysis revealed that all Limestonevirus phages express TSP1-26, thus the results suggest that all phages in the Limestonevirus genus can bind and degrade this LPS. This is in accordance with the known hosts of almost all Limestonevirus phages [14] , [31] , [47] , [48] , [49] , [50] , [51] , [52] , [53] . Finally, TSP2 (TSP2-18) of taipeivirus 0507KN21 recognize the KN2 capsular polysaccharide [17] .…”
Section: Resultssupporting
confidence: 89%
“…Our analysis revealed that all Limestonevirus phages express TSP1-26, thus the results suggest that all phages in the Limestonevirus genus can bind and degrade this LPS. This is in accordance with the known hosts of almost all Limestonevirus phages [14] , [31] , [47] , [48] , [49] , [50] , [51] , [52] , [53] . Finally, TSP2 (TSP2-18) of taipeivirus 0507KN21 recognize the KN2 capsular polysaccharide [17] .…”
Section: Resultssupporting
confidence: 89%
“…Phages completely lost their viability at PH 3 and 13. Our results had agreement with [19] who found that a phage F20 virulent to Enterobacter aerogenes was stable over a broad range of pH from 4 to 11 and with [21] who reported that Enterobacter sp. M4 phage (EspM4VN) was stable from pH 4 to 10 but deactivated at pH 3 and 12.…”
Section: Discussionsupporting
confidence: 91%
“…Only about 30 to 50 % of phage particles survived after treatment at 55 ᴼ C. These findings indicated the high thermal tolerability of isolated phages. Comparatively, thermostable phages from the family Siphoviridae were reported to be stable at 60 ᴼC but their titers were dramatically decreased by 50% at 70 ᴼC [39], also [21] reported that Enterobacter sp. M4 phage (EspM4VN) kept stable infectivity at temperatures 10-50ᴼC but deactivated at 70 ᴼC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SEA, novel phages have been screened using WGS for their lysogenic and endotoxin production potentials (Gan et al, 2013;Lal et al, 2016a;Wirjon et al, 2016;Thanh et al, 2020;Dewanggana et al, 2021;Nuidate et al, 2021), which are important properties to avoid in choosing therapeutic phages. WGS can also aid in the more detailed classification and identification of the phages, as also applied in SEA strains with promising therapeutic potentials (Gan et al, 2013;Hoai et al, 2016;Lal et al, 2016a,b;Wirjon et al, 2016;Sellvam et al, 2018;Handoko et al, 2019;Thanh et al, 2020;Tu et al, 2020;Nuidate et al, 2021). Metagenomic sequencing of phages in the prospect samples will be helpful in the initial screening of phage genomes even before the isolation of the actual virions.…”
Section: Phase One: Extensive Phage Isolation and Characterizationmentioning
confidence: 99%